Subcutaneous regular insulin for the treatment of diabetic ketoacidosis in children. Issue 4 (23rd March 2016) - Cohen, Michal; Leibovitz, Noa; Shilo, Smadar; Zuckerman‐Levin, Nehama; Shavit, Itai; Shehadeh, Naim
Abstract : Background: Diabetic ketoacidosis (DKA) treatment protocols vary, however low‐dose intravenous administration of regular insulin is the standard care for replacing insulin in most centers. Few studies, the majority in adults, demonstrated subcutaneous injection of rapid‐acting insulin every 1–2 hours to be a valid alternative. Objective: To evaluate the efficacy and safety of subcutaneous regular insulin administered every 4 hours in pediatric DKA in a clinical setting. Methods: A retrospective chart review was conducted. Charts of all children treated with subcutaneous regular insulin for DKA and pH ≥ 7.0, between 2007 and 2010, were reviewed. Seventy‐six DKA episodes in 52 patients were included. Data regarding clinical characteristics, response to treatment, and the occurrence of complications were analyzed. DKA episodes in patients with new‐onset diabetes and in those with established diabetes were compared. Results: Mean age was 11.6 ± 4.0 yr. Eighteen episodes occurred in children with new‐onset diabetes. In all episodes, our protocol resulted in recovery from DKA. Median time to DKA resolution (pH > 7.30, HCO3 > 15) was 10.3 (5.5, 14.2) h. The median total insulin dose was 0.05 (0.04, 0.06) (unit/kg/h). During DKA treatment, hypoglycemia occurred in one episode and hypokalemia, mostly mild, was documented in 14. No cardiac arrhythmias, incidents of cerebral edema, or mortality occurred. Conclusion: Subcutaneous regular insulin administered every 4 hours is an effective and safe alternative for the insulin treatment of DKA with pH > 7.0 in children. Such treatment has the potential to simplify insulin administration when compared to either intravenous regular insulin or q1–2 hour subcutaneous rapid insulin and reduce both patient inconvenience and admission costs.